KAJIAN INDEKS PERTANAMAN DAN POLA TANAM PADA SUBAK SADAP TIRIS DAN SUBAK BUKAN SADAP TIRIS DI DAERAH IRIGASI KEDEWATAN, BALI - Dewi, Ratna Komala; Parining, I Nyoman (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2019)
This  research  was  conducted  to  identify  the  cropping  index  as  well  as  the cropping pattern in the subak sadap tiris and not sadap tiris in the Kedewatan Irrigation Area, Bali. The location of the study was selected purposively, namely Subak Mambal (subak not tadah tiris, namely subak which obtained irrigation water directly from the dam) and Subak Temaga (subak sadap tiris, is a subak that get  irrigation  water  from their upstream  subak). Data were  collected  through interviews using a structured questionnaire for 60 farmers, namely in each subak as many as 30 farmers were selected randomly and focus group discussions with pekaseh and heads were dropped during the period June to August 2018. To explore cropping indexes and cropping patterns were analyzed qualitatively descriptive. The results showed that cropping index in subak sadap tiris was 250 with rice-rice cropping pattern, while cropping index in subak not sadap tiris was 200-300 with more varied cropping patterns, namely 66.66% rice-rice cropping  patterns;  16.67%  cropping  pattern  of  rice-rice-flowers/vegetable/corn;  16.67%  cropping pattern  (rice  +  flowers/vegetable/corn)  -  (rice  +  flowers/vegetable/corn).